Clinical rule to decrease antibiotics?. Issue 7 (July 2017) - Covey, Carlton; Moss, David
Abstract : N/A: Hay AD, Redmond NM, Turnbull S, Christensen H, Thornton H, Little P, et al. Development and interval validation of a clinical rule to improve antibiotic use in children presenting to primary care with acute respiratory tract infection and cough: a prognostic cohort study. Lancet Respir Med . 2016; 4(11):902–910.